Menegakkan Hak Beragama di Tengah Pluralisme - Mariyadi Faqih (The Constitutional Court of the Republic of Indonesia, 2016)
The verdict of the Constututional Court (MK) regarding the rejection of Law Trial Number 1/PNPS/Year 1965 about the Prevention of Religion Violation and/or desecration through Indonesia’s Law of Constitution year 1945 can be read as reinforcement through the juridical existence which is related to the right of religion freedom. Any kinds of religion desecration and violation such as a violence in the name of religion or religion radicalism which happens in Indonesia is not caused by the juridical products in the era of the old orde or because of the emergency product, but it is more caused by the compilation of problems such as unfairness, disparity, and powerlessness.